2006
DOI: 10.1095/biolreprod.105.049502
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Mouse Embryonic Stem Cell Subpopulations1

Abstract: We previously demonstrated that mouse embryonic stem (ES) cells show a wide variation in the expression of platelet endothelial cell adhesion molecule 1 (PECAM1) and that the level of expression is positively correlated with the pluripotency of ES cells. We also found that PECAM1-positive ES cells could be divided into two subpopulations according to the expression of stage-specific embryonic antigen (SSEA)-1. ES cells that showed both PECAM1 and SSEA-1 predominantly differentiated into epiblast after the blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…Mouse ES cells have been studied in great detail using such global gene expression profiling. [28][29][30][31][32][33][34] These studies have identified genes important for self-renewal and pluripotency of ES cells, as well as important genes for the formation of germ layers (ectoderm, mesoderm, and endoderm). Analysis of genes specific for ES cell maintenance, germ layers, and hematopoiesis indicated that all three germ layers of embryonic development are generated during bioreactor cultures and that each bioreactor shows a unique gene expression profile, especially for hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse ES cells have been studied in great detail using such global gene expression profiling. [28][29][30][31][32][33][34] These studies have identified genes important for self-renewal and pluripotency of ES cells, as well as important genes for the formation of germ layers (ectoderm, mesoderm, and endoderm). Analysis of genes specific for ES cell maintenance, germ layers, and hematopoiesis indicated that all three germ layers of embryonic development are generated during bioreactor cultures and that each bioreactor shows a unique gene expression profile, especially for hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the majority of genes with a significant change in expression were up-regulated may help to elucidate candidate genes participating in the underlying signalling pathways that control the early differentiation and maturation of mESCs. However, it might be important to note that EBs are composed by many cell types that might be reflected by a higher gene expression pattern in comparison with mESCs.The 3-day-EB cells contained genes related to growth and cell cycle control; Mcm5 gene, which regulates cell growth and is involved in M/G1 and G2/M cell cycle check points and in the assembly of the pre-replicative complex (Kimura et al, 2001); Ccnd2, related to cell cycle control and P53 signalling (>5-fold higher expression) (Furusawa et al, 2006); Prim1, related to S/G1 cell cycle check point and DNA replication initiation (>5-fold higher expression); Fst, related to cell proliferation and growth (Skottman et al, 2006); Txndc1, which participates in the induction of cell growth and proliferation through apoptosis inhibition (>5-fold higher expression) (Harkness et al, 2008); and Tk1, related to nucleotide metabolism and DNA replication. A class of three related genes, Lama1, Lamb1-1 and Lamc1, were also up-regulated at the start of differentiation.…”
mentioning
confidence: 99%
“…In fact, several groups have performed expression microarray analyses at the single-cell level and have revealed populations of cells that differ in their transcript profiles (Crino et al, 1998;Chiang & Melton, 2003;Kurimoto et al, 2006;Ramos et al, 2006;Tang et al, 2010). Several studies, including ours, have found that well-maintained mouse ESC cultures consist of a small percentage of cells that show fluctuating expression levels of genes such as Dppa3 (Stella/Pgc7; Payer et al, 2006;Hayashi et al, 2008), Nanog (Chambers et al, 2007;Singh et al, 2007), Pecam1 (Furusawa et al, 2004;Furusawa et al, 2006), Rex1 (Toyooka et al, 2008) and Zscan4 (Falco et al, 2007;Zalzman et al, 2010), or genes associated with cell differentiation, such as Brachyury/T (Suzuki et al, 2006a;Suzuki et al, 2006b), Rhox6/9 (Carter et al, 2008), Tcf15 and Twist2 (Tanaka et al, 2008). These genes are either downregulated (Nanog and Rex1) or expressed (the rest) in about one-tenth of cells in culture as a steady state ( Fig.…”
Section: Transcriptional Heterogeneity In Pluripotent Stem Cellsmentioning
confidence: 73%